Realisation and measurement of (6–15) keV single‐energy X‐rays. Issue 23 (6th December 2019) - Li, Mengshi; Wu, Jinjie; Lu, Xingqiang; Guo, Siming
Abstract : Since the German physicist Roentgen discovered X‐rays, X‐rays have been widely used in medical diagnostics, industrial non‐destructive testing, and scientific research. There are four main types of single‐energy X‐ray generation: k ‐fluorescence, radioactive sources, X‐ray machines (relying on monochromators), and synchrotron radiation. In view of the advantages of using X‐ray machines to generate continuous energy points and non‐nuclear pollution, this study uses Oxford fluorescent tubes and crystal diffraction methods to generate single‐energy X‐rays. The diffracted crystal uses Si111 and calculates the different energy values obtained by diffracting different Bragg angles. This study uses the silicon drift detector to measure the energy spectrum of (6–15) keV single‐energy X‐rays, the stability of the Oxford fluorescent tube, and spot size with a charge‐coupled device detector. The obtained energy spectrum is compared with the theoretical energy calculated to verify the correctness of this method and provides important reference for crystal diffraction in low‐energy sections.